Borrowing Keep and Its Translation Found In The Text of “Puputan Badung” - Dewa Made Agustawan (International Journal of Linguistics and Discourse Analytics, 2022)
This research aims to describe the equivalence of meaning from the borrowing words of the text. The data is form of narrative text both in Indonesia and English edition about The Story of Puputan Badung especially about The Story of Pregnant Woman. The analysis applied the theory of translation procedure that proposed by Vinay and Darbelnet in Venuti (2000). The process of collecting the data is started by reading the entire data source in order to understand the text. The method of collecting the data, the data source is read to find out the types of borrowing technique found in the “Story of Pregnant Woman”. Based on the result of the analysis, it can be seen that, there are two types of borrowing techniques applied in the story, namely pure borrowing and naturalized borrowing. Those are 4 data were translated in pure borrowing techniques and 1 data that were translated in naturalized borrowing. Also, from the result of the analysis it showed that the dominant type is represented by pure borrowing